Upregulation of microRNA‐7 contributes to inhibition of the growth and metastasis of osteosarcoma cells through the inhibition of IGF1R. Issue 12 (17th May 2019) - Zhang, Zuojun; Zhao, Ming; Wang, Guojie
Abstract: We aim to uncover the methylation of microRNA‐7 (miR‐7) promoter in osteosarcoma (OS) and the inner mechanism of miR‐7 on the progression of OS cells. Expression and methylation state of miR‐7 in OS tissues and cells were detected. With the aim to unearth the ability of miR‐7 in OS, the proliferation, cell cycle progression, apoptosis, invasion, migration of OS cells, and the tumor growth in nude mice were determined. Meanwhile, IGF1R expression was detected and the association between miR‐7 and IGF1R was confirmed. The proliferating cell nuclear antigen (PCNA) expression was tested by immunohistochemical staining, and the lung metastasis was observed by H&E staining. miR‐7 expression was decreased and methylation state of miR‐7 was increased in OS tissues and cells. Upregulated miR‐7 inhibited proliferation, cell cycle progression, invasion, and migration, while inducing apoptosis of OS cells and the tumor growth as well as PCNA expression in nude mice. Expression of IGF1R was downregulated in OS cells with overexpression of miR‐7. Experiments verified the binding site between miR‐7 and IGF1R. Our study demonstrates that abnormal methylation of miR‐7 contributes to decreased miR‐7 in OS. In addition, miR‐7 represses the initiation and progression of OS cells through the inhibition of IGF1R.